Natural sweeteners - Balachandran, Karthik (Journal of Social Health and Diabetes, 2018)
The artificial sweeteners,though marketed as zero calorie food additives, have been found to have several health hazards. Ironically they seem to worsen the metabolic syndrome - the very same disease they are supposed to treat. Natural sweeteners are an alternative to the artificial sweeteners and can be particularly helpful in patients who are newly diagnosed with diabetes. They help in transitioning the patient to a healthier life style. This narrative review, discusses the evidence for and against the use of natural sweeteners in the context of diabetes.
Keywords: Diabetes; natural sweeteners; Stevia